The Relationship Between Educational Philosophy and Educational Theory in the Era of Digital Globalization - Andesman (Zona Education Indonesia, 2023)
Education is born from its mother, namely philosophy, in line with the process of development of science, the science of education is also separated slowly from its parent. In the beginning education was with philosophy, because philosophy could never free itself with the formation of man. Philosophy was created by man for the sake of understanding man's position, human development, and improving human life. This research method is qualitative using descriptive methods. Qualitative data obtained from research results can be used as a source of extensive description and can be based on a strong point of view, and can contain explanations of all processes occurring in the local environment. A philosophizing person is a person who loves truth, is knowledgeable, wise and wise. Understanding based on the book Tashowirrul Islami written by Ali Ahmad Madzkur that in the philosophy of education applies idealistic, realistic, compassion and other principles. The philosophy of education is the application of philosophers in the field of education. The relationship of philosophy with educational theory can be said to be speculative, prescriptive, and analytical